2009
DOI: 10.1002/hed.21077
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the superior thyroid and superior laryngeal arteries

Abstract: Variations in the origin of STA and SLA from the carotid arterial tree and the similarity of their diameters mean that there is a significant possibility of their misidentified during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 7 publications
8
81
1
1
Order By: Relevance
“…This is most common origin of superior thyroid artery. The superior thyroid artery origin from common carotid artery in the present study is 31.25% and similar in other studies [15,16,18,20,21] in a range of 1.51% to 52.3%. This is the second common position in present study.…”
Section: Methodssupporting
confidence: 92%
“…This is most common origin of superior thyroid artery. The superior thyroid artery origin from common carotid artery in the present study is 31.25% and similar in other studies [15,16,18,20,21] in a range of 1.51% to 52.3%. This is the second common position in present study.…”
Section: Methodssupporting
confidence: 92%
“…They have reported 4 different origins for the STA, the most frequent type being from the carotid bifurcation (49%). Similarly, they have reported 4 different origins for the SLA and most frequent type is one in which the artery arose from STA (78%) [4]. Although, standard literature [2] observes that the STA as a branch of the ECA, Lucev et al have reported that STA arises more often from the common carotid artery (47.5% of cases) than from the external carotid artery (30% of cases).…”
Section: Discussionmentioning
confidence: 95%
“…Because of high probability of variations in the arteries of carotid and digastric triangles, a number of studies have been carried out on these arteries and a wide range of variations have been reported. Recently, Vázquez et al have dissected 330 human hemi-necks and studied the variations of superior thyroid and superior laryngeal arteries [4]. They have reported 4 different origins for the STA, the most frequent type being from the carotid bifurcation (49%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En este trabajo, el origen de la arteria tiroidea superior, en todos los bloques estudiados, se puede clasificar como tipo III, de acuerdo a la clasificación propuesta por Vázquez et al (2009), dado que la arteria tiroidea superior siempre se originó de la arteria carótida externa. En contraste con lo encontrado por Vázquez et al, quienes describieron que en el 49% de los casos la arteria tiroidea superior se originaba de la bifurcación de la carótida (tipo I), lo hace 27% de la carótida común (tipo II), directamente de la carótida externa, solamente se originó el 23% y lo clasificaron como tipo III.…”
Section: Discussionunclassified